PENGARUH INSTITITUSIONAL OWNERSHIP, PROPORSI DEWAN KOMISARIS INDEPENDEN DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE: Studi empiris pada perusahaan property dan real estate yang terdaftar di bursa efek indonesia - trisnawati trisna (AKUNTANSI DEWANTARA, 2022)
The purpose of this study was to examine the effect of institutional ownership, the proportion of independent commissioners, and capital intensity on tax avoidance. This study uses quantitative techniques with secondary data from property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020 with a period of 5 years. Purposive sampling was used to make the sample of this study, which included 9 companies. The data analysis method used is panel data regression analysis with the Eviews 10 statistical program. This study shows that institutional ownership, the proportion of independent commissioners and capital intensity simultaneously have a significant effect on tax avoidance, partially institutional ownership has no significant effect on tax avoidance, the proportion independent commissioners and capital intensity have a significant effect on tax avoidance